Experimental transmission of human hepatitis delta virus to the laboratory mouse. - Netter, H J (1993)
Human hepatitis delta virus (HDV), obtained from the serum of an experimentally infected woodchuck, was injected into either the peritoneal cavity or the tail vein of both adult CB17 mice and mice with a severe combined immunodeficiency (CB17-scid mice). Three lines of evidence indicated that the virus was able to reach the liver and infect hepatocytes: (i) the amount of HDV genomic RNA detected in the liver by Northern (RNA) analysis increased during the first 5 to 10 days postinoculation, reaching a peak that was about threefold the amount in the original inoculum; (ii) also detected in the liver was the viral antigenomic RNA, which is complementary to the genomic RNA found in virions, and is diagnostic for virus replication; and (iii) by immunoperoxidase staining of liver sections, the delta antigen was detected in the nuclei of scattered cells identifiable as hepatocytes. In all of the mice, clearance of the infection occurred between 10 and 20 days after inoculation. The half-life for clearance was about 3 days in CB17-scid mice, indicating that clearance of infection did not involve a T- and B-cell-dependent immune response. Cell-to-cell spread of the initial infection was not detected. One possible interpretation of our results is that HDV infection of hepatocytes is directly cytopathic. Also, the results imply that chronic infection of the liver in humans may require continuous spread of virus within the liver. Alternatively, HDV in the absence of helper virus may be unable to cause a chronic infection of hepatocytes in vivo.